A single blood eosinophil count measurement is as good as two for prediction of ICS treatment response in the IMPACT trial. Issue 3 (23rd September 2021) - Bafadhel, Mona; Barnes, Neil; Bourke, Stephen C.; Compton, Chris; Criner, Gerard J.; Dransfield, Mark T.; Halpin, David M.G.; Han, MeiLan K.; Hartley, Benjamin; Jones, C. Elaine; Lange, Peter; Lettis, Sally; et al.
Blood eosinophil count is a readily available biomarker in COPD that can assist identification of patients most likely to benefit from inhaled corticosteroids (ICS) [1]. Recent evidence has demonstrated a link between blood eosinophil count as a continuous variable and magnitude of response to ICS in terms of exacerbation rate reduction [2, 3]. The current Global Initiative for Chronic Obstructive Lung Disease (GOLD) report recommends that blood eosinophil count can be used to predict the likelihood of beneficial response to ICS, in combination with clinical assessment of exacerbation risk [1]. However, as blood eosinophil counts can show variability, particularly at higher levels [4–6], it is of clinical interest to determine how many measurements are sufficient to predict an ICS response in patients with COPD. Data from the InforMing the PAthway of COPD Treatment (IMPACT) trial showed an association between blood eosinophil count and ICS response on reduction of moderate/severe COPD exacerbations [3]. This post hoc analysis of IMPACT compared whether one or two measurements of blood eosinophil count can better predict ICS responses in patients with COPD. This post hoc analysis of the IMPACT trial demonstrated that a single blood eosinophil count measurement is sufficient to predict a beneficial response to inhaled corticosteroids in patients with symptomatic COPD and a history of exacerbations https://bit.ly/3wgeDCU